2006
DOI: 10.1111/j.1744-7348.2005.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulated beetle defoliation on willow genotypes in mixture and monotype plantations

Abstract: The effect of simulated beetle damage (0%, 25%, 50% and 75% mechanical defoliation) on 12 willow genotypes, grown in short-rotation coppice, was studied in a modified criss-cross experimental design. The design enabled the aboveground effects of monoculture and mixed planting to be assessed. Repeated measurements were modelled to produce derived variables in terms of time or, more appropriately, in terms of accumulated day length (i.e. 'developmental time') units. These derived variables were then analysed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…A common procedure to study the effects of leaf area loss on the growth and yield of plants is the simulation of leaf feeding of phyllophagous pest insects by artificial defoliation [24,[29][30][31][32]. The main advantage of this procedure is the ability to precisely control and modify the extent, number, and timing of defoliation, whereas the difference in the duration between natural and artificial defoliation as well as the potential lack of herbivore-induced plant volatiles due to a merely mechanical damage are disadvantageous [30,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…A common procedure to study the effects of leaf area loss on the growth and yield of plants is the simulation of leaf feeding of phyllophagous pest insects by artificial defoliation [24,[29][30][31][32]. The main advantage of this procedure is the ability to precisely control and modify the extent, number, and timing of defoliation, whereas the difference in the duration between natural and artificial defoliation as well as the potential lack of herbivore-induced plant volatiles due to a merely mechanical damage are disadvantageous [30,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…and Populus spp. have genetic and morphological distinctness (Karrenberg et al 2002, Zalesny et al 2005; also ecological differences emerge in studies comparing genus, species or hybrids in traits as tolerance to damage (Nordman et al 2005, Powers et al 2006, growth strategies adopted throughout the season (Tharakan et al 2005), root development (McIvor et al 2013), suitability for phytoremediation purposes (Dos Santos et al 2007, Borghi et al 2008 or suitability for short rotation coppice (Laureysens et al 2005, Tharakan et al 2005. Thus, this versatility in plant characteristics of poplars and willows would explain the differences in responses to defoliation observed in our study.…”
Section: Discussionmentioning
confidence: 65%
“…In poplars, Bassman et al (1982) observed reductions in height and diameter growth of about 20 % and Reichenbacker et al (1996) recorded reductions in height and diameter growth of 12 % and 9 %, respectively. In willows, Powers et al (2006) reported a reduction in height growth between 5 and 20 %; whereas Peacock et al (2002) observed a significant increase in height in only one of the eleven tested hybrids of Salix viminalis L. Differences in tree growth among studies may be caused by multiple factors including genetic variation among clones or environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential stem elongation is modelled using a linear function of day length multiplied by a Heaviside function for the effect of daily average air temperature ( Powers et al , 2006 ) (Eq. S5 at JXB online).…”
Section: Methodsmentioning
confidence: 99%